2021
DOI: 10.1002/admi.202100309
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electromechanical Response and Thermal Stability of 0.93(Na1/2Bi1/2)TiO3‐0.07BaTiO3 Through Aerosol Deposition of Base Metal Electrodes

Abstract: Na1/2Bi1/2TiO3‐based relaxor ferroelectrics are extensively investigated for use in transduction applications because of their relatively large electromechanical properties. Integration of these materials into devices, however, requires better temperature stability in addition to electromechanical properties. This work demonstrates a novel approach to enhance the temperature stability of the long‐range ferroelectric order as well as to enhance electromechanical properties in a non‐ergodic relaxor 0.93(Na1/2Bi1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…For the BNT−7BT substrate using the aerosol deposition of an electrode, the deposition-induced residual stresses result in long-range ferroelectric domain ordering. 49 These results reveal that the evolution of the domain structure is supposed to be caused by the increased R phase and residual stresses.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…For the BNT−7BT substrate using the aerosol deposition of an electrode, the deposition-induced residual stresses result in long-range ferroelectric domain ordering. 49 These results reveal that the evolution of the domain structure is supposed to be caused by the increased R phase and residual stresses.…”
Section: Resultsmentioning
confidence: 84%
“…The increase in ⟨ξ⟩ means that the incorporation of Ag significantly increases the local polar ordering and mean size of the domain structure. Larger domain sizes and enhanced ferroelectric ordering usually favor delayed thermal depolarization behavior . Note that there is a strong dependence between the domain and phase structure. , For example, complex domains of about 100 nm were observed in the BNT–4BT ceramics with the R phase, while the BNT–6BT (MPB) ceramics consisted mainly of nanometer-sized domains. , Meanwhile, the domain pattern of BNT-based materials is also affected by the stresses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of metal films by AD is still in its early stages. Thus far, AD has been used to deposit metal films such as Cu [16,17], Ag [15,18], Fe [19,20] and Fe-based amorphous alloys [21]. In this study, we have deposited metal layers of Al, which has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%